Partisipasi Pemerintah dan Masyarakat Desa Nogosaren Kecamatan Gading dalam Mengurangi Kerusakan Hutan Produksi Berdasarkan PP No.26 Tahun 2020 tentang Rehabilitasi dan Reklamasi Hutan - mohammad maulana jakfar (Jurnal Hukum Lex Generalis, 2026)
Production forest destruction is a serious environmental problem that disrupts the balance of the ecosystem and the sustainability of community life. According to Government Regulation Number 26 of 2020 concerning Forest Rehabilitation and Reclamation, the participation of village governments and communities is crucial in restoring forest function. This study aims to analyze the forms of participation of village governments and communities in Nogosaren Village, Gading District, and the factors that influence it according to the PP. Using qualitative empirical legal methods through interviews, observations, and literature studies, the results show that participation has been carried out through forest rehabilitation, informal supervision, and socialization, but it is still not optimal and has not been legally institutionalized. Influencing factors include legal, institutional, sociocultural, economic, and environmental legal awareness. The study concludes that strengthening village regulations, increasing the capacity of apparatus, and community awareness are key to optimizing participation for sustainable production forest management according to PP No. 26 of 2020.